Possibility of using waste water energy to generate electricity using small design hydropower technology throughout home pipeline: article / Muhammad Faiz Yusoff - Yusoff, Muhammad Faiz (2014)
Small design hydropower technology was used to generate electricity instead of flowing water. The system of hydropower design should be able to generate power, use a pressure water instead of flowing water to rotate the turbine and can be applied on domestic pipeline. Three different permanent magnet direct current motors were tested in order to observe the performance in generating electricity. Water pressure gauge and valve were used to observe the pressure and control the water pressure instead of water flowing. In this paper, the greater the pressure the greater the power was produced. Moreover, the speed of water increased when nozzle was used. The result showed the water turbine rotated in high speed when the speed of water flow was increased. In addition, this paper presented the experimental setup system and the result of the experiment. From the experiment, the power generated by the system directly proportional to the speed of the water turbine rotation. This paper found that the small design hydropower technology instead of flowing water able to produce electricity.